2008
DOI: 10.1073/pnas.0712244105
|View full text |Cite
|
Sign up to set email alerts
|

A W-linked DM-domain gene, DM-W, participates in primary ovary development in Xenopus laevis

Abstract: In the XX/XY sex-determining system, the Y-linked SRY genes of most mammals and the DMY/Dmrt1bY genes of the teleost fish medaka have been characterized as sex-determining genes that trigger formation of the testis. However, the molecular mechanism of the ZZ/ZW-type system in vertebrates, including the clawed frog Xenopus laevis, is unknown. Here, we isolated an X. laevis female genome-specific DM-domain gene, DM-W, and obtained molecular evidence of a W-chromosome in this species. The DNA-binding domain of DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
450
3
13

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 457 publications
(475 citation statements)
references
References 25 publications
9
450
3
13
Order By: Relevance
“…However, this need not represent identity by descent, for a flatfish also has a ZW sex pair with homology to the bird ZW, and uses DMRT1 dosage to determine sex 32. DMRT1 has also been pressed into service independently by spawning copies that became a dominant male‐determiner in medaka 16, 65 or female determiner in Xenopus 66; clearly this gene is simply good at sex determination and has been independently recruited in several lineages 67.…”
Section: Sex Chromosome Changes Define the Three Major Mammal Groupsmentioning
confidence: 99%
“…However, this need not represent identity by descent, for a flatfish also has a ZW sex pair with homology to the bird ZW, and uses DMRT1 dosage to determine sex 32. DMRT1 has also been pressed into service independently by spawning copies that became a dominant male‐determiner in medaka 16, 65 or female determiner in Xenopus 66; clearly this gene is simply good at sex determination and has been independently recruited in several lineages 67.…”
Section: Sex Chromosome Changes Define the Three Major Mammal Groupsmentioning
confidence: 99%
“…In addition, dmy/dmrt1Yb is only found in two subspecies among more than 20 related species of medaka (Matsuda et al, 2003). Over the past several years, sex-determining genes 25 have been identified in numerous lower vertebrates, including dm-W in the amphibian Xenopus laevis (Yoshimoto et al, 2008) and gsdfY, amhY, sdY, amhr2 and sox3 in a suite of species of teleost fish, i.e., a medaka-related fish, (Oryzias luzonensis) (Myosho et al, 2012), Patagonian pejerrey (Odontesthes bonariensis) (Hattori et al, 2012), rainbow trout (Onchorhynchus mykiss) (Yano et al, 2012), tiger pufferfish (Takifugu rubripes) (Kamiya et al, 2012), and another 30 medaka-related fish (Oryzias dancena) (Takehara et al, 2014), respectively. Thus, in contrast to many other developmental processes, evolutionary diversity exists in the initial switches of sex determination.…”
Section: Introductionmentioning
confidence: 99%
“…Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1. Because of the high evolutionary conservation and the newly recruited role in vertebrates (Herpin and Schartl, 2011;Xia et al, 2007), Dmrt1 also allows us to analyze the evolutionary history of genome duplication through examination of divergence and phylogeny of the duplicated genes.…”
Section: Introductionmentioning
confidence: 99%